(3GdJShjb GdSjGMj (B:s (3eONd Sdhcj (B/s - (3YHjOGJ, eMeOs ((3YeGf(B: s (3OGQ hGFd(B, s, 2000)
(3ebOeI aj GdJShjb GdSjGMj(B-(3GdHjFI aj GdJShjb GdSjGMj(B-(3JLRFI GdCShGb GdSjGMjI(B-(3GdJNWjW GdESJQGJjLj ddJShjb GdSjGMj(B-(3GSJQGJjLjI GdefJL GdSjGMj(B-(3GSJQGJjLjI JSYjQ GdefJL GdSjGMj(B-(3GSJQGJjLjI JhRjY GdefJL GdSjGMj(B-(3GSJQGJjLjI JQhjL GdefJL GdSjGMj(B-(3GdSjGMI GdOjfjI(B-(3GdSjGMI GdJQGKjI(B-(3GdSjGMI GdELJeGYjI(B-(3MGdI OQGSjI(B((3ehbY GdHJQGA GdSjGMj(B)-(3MGdI OQGSjI dehbY GdHMQ GdejJs
Keywords: (3GdJShjb (B- (3GdGQOfs; (3GdSjGMI (B- (3GdGQOfs